Development of a Community-Based Business Model Utilizing Solar Energy and Net Metering: A Case Study of Community Enterprises in Chanthaburi Province, Thailand - Ruttanawijit, Kornpaphop; Kamtai, Artit; Chanthasit, Kritsana (Srinakharinwirot University Engineering Journal, 2025)
This study aims to design and develop a community energy business model by applying a solar photovoltaic (PV) system with Net Metering to reduce energy expenses among community enterprises in Chanthaburi Province. The research employed a mixed-methods approach, including a twelve-month retrospective analysis of electricity bills and in-depth interviews with 15 target community groups across both urban and rural areas. Statistical analysis revealed that rural community enterprises had a higher average energy cost of 5.20 THB/kWh compared to 4.50 THB/kWh in urban areas, primarily due to outdated technology and inadequate infrastructure. Cluster analysis using K-Means classified the enterprises into two groups; Cluster 0 (low energy use with high costs) and Cluster 1 (high energy use with high costs), providing insights for designing tailored energy and technology strategies. The business model was developed using the Business Model Canvas (BMC) framework, covering nine core components. An economic feasibility assessment of the Net Metering system showed a levelized cost of electricity (LCOE) at 2.21 THB/kWh, significantly lower than the regional utility rate of 4.10 THB/kWh. The internal rate of return (IRR) was approximately 13.5%, affirming the investment’s viability and its potential scalability to other communities with similar contexts. Importantly, community participation was identified as a key factor for ensuring the long-term sustainability of decentralized energy systems.